Influence of Fluid-Induced Forces on Cavitating Turbopumps Rotordynamics in Forced Whirl Experiment. Issue 1 (May 2021) - Bertelli, F.; Pasini, A.; Bottai, R.
Abstract: As typically highlighted in the experimental results, in unshrouded axial inducers the fluid-induced rotordynamic forces are significantly dependent on the flow coefficient and do not present a quadratic behavior with respect to the whirl ratio, as commonly reported in radial pumps. Moreover these forces show destabilizing peaks that typically increase with decreasing cavitation number. The present paper illustrates the development of a theoretical model of the rotordynamic system capable of assessing the influence of fluid-induced rotordynamic forces on the dynamic response of turbopumps under cavitating/non-cavitating conditions. The implementation of the fluid-induced rotordynamic forces in the dynamic model has been proposed through the so-called F.I.R.F. model, which is applied to a test set-up for forced whirl experiments, in order to characterize the whirl natural frequencies and the relative mode shapes. The model has been successfully applied to a rotordynamic system including an unshrouded axial inducer and the corresponding computed critical speeds are summarized in the Campbell diagrams pointing out the difference between dry and wet analysis results.